Pengaruh Digitalisasi Keuangan Syariah Terhadap Inklusi Keuangan UMKM di Indonesia - Laila Murningsih Novrian Wakhidah; Shelvyna Rikantasari; Mutammimatur Rahmah Ramadhana; Muhammad Izzudin Farhans (JOURNAL OF SHARIA ECONOMICS, 2025)
The digitalization of Islamic finance is growing rapidly in line with the increasing demand for inclusive, efficient, and sharia-compliant financial services. Micro, Small, and Medium Enterprises (MSMEs), as the backbone of the national economy, still face limited access to formal financial services. This study aims to analyze the impact of the digitalization of Islamic finance on the financial inclusion of MSMEs in Indonesia. The research method used a quantitative approach with a survey of MSMEs using digital Islamic financial services. Data were analyzed through validity, reliability, and linear regression tests. The results show that the digitalization of Islamic finance has a positive and significant impact on the financial inclusion of MSMEs. This finding indicates that the digitalization of Islamic finance contributes to the achievement of the maqasid sharia through increasing economic welfare.